Ferroelectric Control of Organic/Ferromagnetic Spinterface. Issue 46 (6th October 2016) - Liang, Shiheng; Yang, Hongxin; Yang, Huaiwen; Tao, Bingshan; Djeffal, Abdelhak; Chshiev, Mairbek; Huang, Weichuan; Li, Xiaoguang; Ferri, Anthony; Desfeux, Rachel; Mangin, Stéphane; Lacour, Daniel; et al.
Abstract : Organic multiferroic tunnel junctions based on La0.6 Sr0.4 MnO3 /poly(vinylidene fluoride) (PVDF)/Co structures are fabricated. The tunneling magneto‐resistance sign can be changed by electrically switching the ferroelectric polarization of PVDF barrier. It is demonstrated that the spin‐polarization of the PVDF/Co spinterface can be actively controlled by tuning the ferroelectric polarization of PVDF. This study opens new functionality in controlling the injection of spin polarization into organic materials via the ferroelectric polarization of the barrier.